Über eine Klasse der invariantischen affinischen Zusammenhänge auf einer Lie Gruppe - Vosylius, R. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. В. Восилюс. Об одном классе инвариантных аффинных связностей на группах ЛиR. Vosylius. Apie vieną invariantinių afininių sąryšių Li grupėje klasę